Bi-allelic ADARB1 Variants Associated with Microcephaly, Intellectual Disability, and Seizures - Tan, Tiong Yang; Sedmík, Jiří; Fitzgerald, Mark P; Halevy, Rivka Sukenik; Keegan, Liam P; Helbig, Ingo; Basel-Salmon, Lina; Cohen, Lior; Straussberg, Rachel; Chung, Wendy K; Helal, Mayada; Maroofian, Reza; et al. (American journal of human genetics, 2020)
The RNA editing enzyme ADAR2 is essential for the recoding of brain transcripts. Impaired ADAR2 editing leads to early-onset epilepsy and premature death in a mouse model. Here, we report bi-allelic variants in ADARB1, the gene encoding ADAR2, in four unrelated individuals with microcephaly, intellectual disability, and epilepsy. In one individual, a homozygous variant in one of the double-stranded RNA-binding domains (dsRBDs) was identified. In the others, variants were situated in or around the deaminase domain. To evaluate the effects of these variants on ADAR2 enzymatic activity, we performed in vitro assays with recombinant proteins in HEK293T cells and ex vivo assays with fibroblasts derived from one of the individuals. We demonstrate that these ADAR2 variants lead to reduced editing activity on a known ADAR2 substrate. We also demonstrate that one variant leads to changes in splicing of ADARB1 transcript isoforms. These findings reinforce the importance of RNA editing in brain development and introduce ADARB1 as a genetic etiology in individuals with intellectual disability, microcephaly, and epilepsy.
Keywords: Genetic Predisposition to Disease; alely; mikrocefalie; záchvaty; migrating focal seizures; Alleles; HEK293 Cells; Intellectual Disability; alternativní sestřih; sestřih RNA; mužské pohlaví; epilepsy; genetická variace; mentální retardace; Seizures; RNA-Binding Proteins; Adenosine Deaminase; dítě; Child; Genetic Variation; Child, Preschool; intellectual disability; Alternative Splicing; HEK293 buňky; předškolní dítě; Humans; proteiny vázající RNA; Microcephaly; microcephaly; RNA editing; adenosindeaminasa; ADAR2; genetická predispozice k nemoci; RNA Splicing; lidé; Male